2016
DOI: 10.1093/jrr/rrv089
|View full text |Cite
|
Sign up to set email alerts
|

Non-induction of radioadaptive response in zebrafish embryos by neutrons

Abstract: In vivo neutron-induced radioadaptive response (RAR) was studied using zebrafish (Danio rerio) embryos. The Neutron exposure Accelerator System for Biological Effect Experiments (NASBEE) facility at the National Institute of Radiological Sciences (NIRS), Japan, was employed to provide 2-MeV neutrons. Neutron doses of 0.6, 1, 25, 50 and 100 mGy were chosen as priming doses. An X-ray dose of 2 Gy was chosen as the challenging dose. Zebrafish embryos were dechorionated at 4 h post fertilization (hpf), irradiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…zebrafish embryos) were irradiated using Neutron exposure Accelerator System for Biological Effect Experiments (NASBEE) facility at the National Institute of Radiological Sciences (NIRS), Chiba, Japan [6]. Furthermore, similar discrepancies were also present in terms of RAR, in which the failure of neutrons to induce RAR in zebrafish embryos and human lymphocytes has been previously reported [7,8] and in contrast, the induction of RAR in Chinese hamster V79 cells was reported in the previous work of Marples and Shov [9]. …”
Section: Introductionmentioning
confidence: 90%
“…zebrafish embryos) were irradiated using Neutron exposure Accelerator System for Biological Effect Experiments (NASBEE) facility at the National Institute of Radiological Sciences (NIRS), Chiba, Japan [6]. Furthermore, similar discrepancies were also present in terms of RAR, in which the failure of neutrons to induce RAR in zebrafish embryos and human lymphocytes has been previously reported [7,8] and in contrast, the induction of RAR in Chinese hamster V79 cells was reported in the previous work of Marples and Shov [9]. …”
Section: Introductionmentioning
confidence: 90%
“…[ 5 ] and Ng et al . [ 6 ] demonstrated that neutrons failed to induce a RAR in human lymphocytes and zebrafish embryos, respectively. In contrast, Marples and Shov [ 7 ] revealed a neutron-induced RAR in Chinese hamster V79 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis was also used as the biological endpoint in many previous studies on radiobiological effects in zebrafish embryos (see e.g., [27,33,35,36,37,38,42,43,45,46,47,48,49]. As reviewed in [39], the extra apoptotic events developed in irradiated zebrafish embryos likely reflected genomic instability induced in the irradiated cells (at 5 hpf), since these irradiated cells and their earlier progeny, which were unstable and mutation prone, had appeared to be healthy and were able to survive many generations before the apoptosis pathways were initiated (at 20, 24, or 30 hpf).…”
Section: Discussionmentioning
confidence: 99%